Diaphragm relaxation causes seizure-related apnoeas in chronic and acute seizure models in rats - Karolína Liška; Aakash Pant; John G.R. Jefferys (Neurobiology of Disease)
Ictal central apnoea is a feature of focal temporal seizures. It is implicated as a risk factor for sudden unexpected death in epilepsy (SUDEP). Here we study seizure-related apnoeas in two different models of experimental seizures, one chronic and one acute, in adult genetically-unmodified rats, to determine mechanisms of seizure-related apnoeas. Under general anaesthesia rats receive sensors for nasal temperature, hippocampal and/or neocortical potentials, and ECG or EMG for subsequent tethered video-telemetry. Tetanus neurotoxin (TeNT), injected into hippocampus during surgery, induces a chronic epileptic focus. Other implanted rats receive intraperitoneal pentylenetetrazol (PTZ) to evoke acute seizures. In chronically epileptic rats, convulsive seizures cause apnoeas (9.9 ± 5.3 s; 331 of 730 convulsive seizures in 15 rats), associated with bradyarrhythmias. Absence of EEG and ECG biomarkers exclude obstructive apnoeas. All eight TeNT-rats with diaphragm EMG have apnoeas with no evidence of obstruction, and have apnoea EMGs significantly closer to expiratory relaxation than inspiratory contraction during pre-apnoeic respiration, which we term “atonic diaphragm”. Consistent with atonic diaphragm is that the pre-apnoeic nasal airflow is expiration, as it is in human ictal central apnoea. Two cases of rat sudden death occur. One, with telemetry to the end, reveals a lethal apnoea, the other only has video during the final days, which reveals cessation of breathing shortly after the last clonic epileptic movement. Telemetry following acute systemic PTZ reveals repeated seizures and seizure-related apnoeas, culminating in lethal apnoeas; ictal apnoeas are central – in 8 of 35 cases diaphragms initially contract tonically for 8.5 ± 15.0 s before relaxing, in the 27 remaining cases diaphragms are atonic throughout apnoeas. All terminal apnoeas are atonic. Differences in types of apnoea due to systemic PTZ in rats (mainly atonic) and mice (tonic) are likely species-specific. Certain genetic mouse models have apnoeas caused by tonic contraction, potentially due to expression of epileptogenic mutations throughout the brain, including in respiratory centres, in contrast with acquired focal epilepsies. We conclude that ictal apnoeas in the rat TeNT model result from atonic diaphragms. Relaxed diaphragms could be particularly helpful for therapeutic stimulation of the diaphragm to help restore respiration.